Impelentasi UU Cipta Kerja Sebagai Instrumen Perwujudan Kesejahteraan Rakyat Perspektif Teori Perjuangan Kelas Karl Marx - Nor Alia; Muhsin Aseri; Tri Hidayati (Journal of Economic and Business Law Review, 2025)
This article analyzes the implementation of the Job Creation Law as a tool to achieve public welfare through Karl Marx’s conflict theory, focusing on historical materialism and class struggle. Intended to boost investment, employment, and ease of doing business, the law has sparked controversy and widespread protests. Although enacted, it was declared unconstitutional by the Constitutional Court in November 2021. Using a descriptive qualitative method and library research, this study draws on articles, books, and online sources, analyzed through Marxist theory. Findings suggest that while the law aimed to support economic recovery post-pandemic, several of its regulations still require collective attention to truly realize its goal of public welfare.